2014
DOI: 10.3233/mnm-140001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of date palm fruit (Phoenix dactylifera L.) on the hormone 17-ß-estradiol in 7,12-dimethylbenz(a)anthracene-induced mammary cancer in rats

Abstract: The effect of date palm fruit feeding (to female Sprague-Dawley rats with 7,12-dimethylbenz(␣)anthracene-induced mammary cancer) on the hormone 17-␤-estradiol concentration was compared to that of feeding soybean seeds and injection with two drugs (one preventive against and the other curative for 7,12-dimethylbenz(␣)anthracene-induced mammary cancer i,e. tamoxifen and the hormone 17-␤-estradiol). The date palm fruit raised the hormone concentration significantly (p < 0.05). The hormone concentration was posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Al-Sayyed et al reported the potential cancer preventive effects of date fruit. They found that increase consumption of dried date fruit reduced significantly the incidence rate of mammary cancer, palpable tumor multiplicity, tumor size and weight compared to the positive control group (Al-Sayyed et al, 2014 ). Eid et al studied the whole date fruit extract and its polyphenol-rich extract, both extracts were prepared from methanol/water (4:1, v/v) containing 10% of 1 molar sodium fluoride (NaF) solution, found to inhibit Caco-2 cell growth, indicating that both were capable of probably acting as anti-proliferative agents in-vitro .…”
Section: Therapeutic Optionsmentioning
confidence: 98%
“…Al-Sayyed et al reported the potential cancer preventive effects of date fruit. They found that increase consumption of dried date fruit reduced significantly the incidence rate of mammary cancer, palpable tumor multiplicity, tumor size and weight compared to the positive control group (Al-Sayyed et al, 2014 ). Eid et al studied the whole date fruit extract and its polyphenol-rich extract, both extracts were prepared from methanol/water (4:1, v/v) containing 10% of 1 molar sodium fluoride (NaF) solution, found to inhibit Caco-2 cell growth, indicating that both were capable of probably acting as anti-proliferative agents in-vitro .…”
Section: Therapeutic Optionsmentioning
confidence: 98%
“…Although, [45] showed that extractable polyphenols (EPP) from Ajwa date fruits were cytotoxic against other cancer cell lines such as hepatocellular carcinoma (HCT-116). Al-Sayyed, et al [46] found that increasing consumption of dried date fruit reduced significantly the incidence rate of mammary cancer, palpable tumour multiplicity, tumour size and weight compared to the positive control group. In another study, Eid, et al [47] studied the effect of the whole date fruit extract and its polyphenol-rich extract, which were prepared from methanol/water (4:1, v/v) containing 10% of 1 molar sodium fluoride (NaF) solution, on the Caco-2 cell lines.…”
Section: Evaluation Of Solvent/sample Ratiomentioning
confidence: 99%
“…Also, the dates quercetin and kaempferol showed high cytotoxic activity against pc3 cells ( 69 , 70 ). Another in vitro study was conducted by Al-Sayyed et al ( 71 ) and reported that Barhi date palm fruit prevents 7,12-Dimethylbenzathracene (DMBA)-induced mammary cancer. Its outcomes can be correlated with the other two drugs, i.e., tamoxifen and 17-β-estradiol.…”
Section: Discussionmentioning
confidence: 99%